Vsebinsko znanje in naravoslovno razmišljanje - Strnad, Janez (Obzornik za matematiko in fiziko, 2009)
An experiment in which the abilities of American and Chinese freshmen in physics were assesed is briefly reported. Thereby in the first step content knowledge in mehanics and electromagnetism and in the second step the ability of science reasoning were established. In the first step the Chinese, who have had more physics in high school, scored much better then Americans. In the second step there was no difference. Can the results give useful clues for physics teachers in our high school?
Keywords: elektromagnetizem; fizika; mehanika; poučevanje fizike; vsebinsko znanje; zmožnost razmišljanja